Analisis Penilaian Kriteria Green Building Pada Pasar Kanigoro Berdasarkan GBCI - Mohammad Kharis Solikan; Trisno Widodo; Risma Dwi Atmajayani (Journal of Science Nusantara, 2024)
The term "green building" denotes buildings that prioritize enhancing health and comfort, with a primary goal of minimizing energy and water usage and reducing environmental impact. The assessment of green buildings at Kanigoro Market considers various criteria such as building appropriateness, land utilization, energy efficiency, water preservation, sustainable materials, indoor air quality, and environmental management. This evaluation adheres to the guidelines established by the Green Building Council Indonesia (GBCI). Buildings are classified into platinum, gold, silver, or bronze categories based on the assessment results, reflecting their environmental sustainability performance levels.